Circularly Polarized Luminescent Carbon Dot Nanomaterials of Helical Superstructures for Circularly Polarized Light Detection. Issue 23 (9th October 2018) - Zheng, Hongzhi; Ju, Bo; Wang, Xiaojun; Wang, Wenhui; Li, Minjie; Tang, Zhiyong; Zhang, Sean Xiao‐An; Xu, Yan
Abstract: Circularly polarized luminescent carbon dot nanomaterials of self‐organized helical superstructures based on cellulose nanocrystals enable strong, right‐handed, and multicolor tunable circularly polarized luminescence with extraordinary dissymmetry factors up to −0.74. The effects of emission intensity and carbon dots loading on the strength of the right‐handed circularly polarized luminescence are experimentally observed and theoretically explained. Potentials of the carbon dots–cellulose nanomaterials for circularly polarized light detection are demonstrated. Abstract : Endowing carbon dots with strong and tunable circularly polarized luminescence is achieved by an evaporation‐induced corporative assembly with cellulose nanocrystals. The potential of the carbon dots–cellulose nanomaterials for circularly polarized light detection is demonstrated.